PERKEMBANGAN KEWENANGAN PEMBERIAN PERSETUJUAN PEMERIKSAAN NOTARIS UNTUK KEPENTINGAN PROSES PERADILAN - , Priharti Dewi Damayanti Yudakusuma, SH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sometimes, the notary, in carrying out their problems, stumble to legal issues that make them have to be investigated by the law enforcements for judicial processâ need. In this regard, this research aims to assess the authority of approval granting to investigate the certain notary for the necessity of judicial process based on Indonesian regulation, Act Number 30, issued in 2004, about incumbency of notary public and approval granting to investigate certain notary for the necessity of judicial process after Indonesian government regenerate, viz. Act Number 2, issued in 2014, related to amendment of the Indonesian regulation above (Act Number 30, issued in 2004) about the incumbency of notary. Research carried out by juridical empirical research method, using primary data and secondary data. Primary data obtained through interviews with respondents, meanwhile the secondary data obtained from literature sources that derived from primary, secondary, and tertiary legal materials. Overall data was analyzed by qualitative analysis method and presented in the form of descriptive analysis. From this research, we can see that based on Indonesian regulation, Act Number 30, issued in 2004, about the incumbency of notary, the approval granting to investigate certain notary for the necessity of judicial process, in the beginning, was given by regional inspectorate board of notary public, Majelis Pengawas Daerah. Since the Indonesian constitutional court, Mahkamah Konstitusi, issued new resolution Number 49/PUU-X/2012 dated at May 28th , 2012, that remove the phrase of âby approval of Regional inspectorate board of notary publicâ (âdengan persetujuan Majelis Pengawas Daerahâ) on regulation at clause 66 paragraph (1) Undang-Undang Nomor 30, issued in 2004 about the incumbency of notary. After Indonesian regulation Act Number 2, issued in 2014 about The Resolution of Act Number 30, issued in 2004 related to the incumbency of notary, The authority of approval granting to investigate certain notary for the necessity of judicial process reappears and become the responsibility of Notary Honorary Board, Majelis Kehormatan Notaris.